From the house to the neighborhood and from the neighborhood to the city. An analysis of the urban trajectories of young Peruvians in the city of Córdoba, Argentina - Zenklusen, Denise (2022)
The following work proposes to reflect on the articulation between migration, youth and urban space, starting from contemplating and reconstructing the ways of inhabiting, circulating and producing the city. From an ethnographic approach, based on in-depth interviews, participant observation and annotated tours, it analyzes the daily and urban trajectories of young Peruvians who live in two peripheral neighborhoods in the city of Córdoba, Argentina. The results show the central place that Peruvian youth occupy in family migration projects and, specifically, in the production of three spaces: the house, the neighborhood and the city. At the same time that these spaces determine the ways of being young.